Identifikasi Hiperbilirubinemia pada Neonatus Menggunakan Metode Jendrassik-Grof di RS Nyi Ageng Serang Yogyakarta - Fritia Sy Dokliwan; Arif Yusuf Wicaksana; Isnin Aulia Ulfah Mu’awanah (Universitas Muhammadiyah Manado, 2026)
Hyperbilirubinemia is a normal condition that occurs in newborns during the first week of birth. This condition is important to note because too high bilirubin levels can lead to complications that can attack the brain such as the incidence of encephalopathy and the incidence of cerebral palsy in infants if left unchecked. This study aims to identify the incidence rate of hyperbilirubinemia in Nyi Ageng Serang Hospital Yogyakarta. This research method uses quantitative research with a cross sectional approach, which uses secondary data, namely data obtained from other parties or agencies. This study used total sampling because all data in this study were used during the 2021 period. The data obtained were analyzed using the SPSS 25.0 program using univariate, bivariate, Chi-Square and Odds Ratio tests. The results of this study showed that the proportion of neonates experiencing hyperbilirubinemia was 30.1% of a total of 558 subjects, while 69.9% did not experience hyperbilirubinemia, with the majority being delivered through normal birth. The Chi-Square test obtained a p-value of 0.582, indicating that there was no significant association between Caesarean delivery and the incidence of hyperbilirubinemia at Nyi Ageng Serang Hospital Yogyakarta in 2021. This is because the number of patients with less months neonates who were treated was less than the number of patients with full months neonates.